Evaluation of influence of coagulation/flocculation and Fenton oxidation with iron on landfill leachate treatment - Smaoui, Yosr; Mseddi, Salma; Ayadi, Najla; Sayadi, Sami; Bouzid, Jalel (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
Landfill leachates (LFL) collected from Sfax (Tunisia) discharge area are characterized by high chemical oxygen demand (COD), ammonium and salts contents. They constitute a source of phytotoxicity and pollution for ground water and surface water resources which requires an adequate treatment process. To evaluate the efficiency of the coagulation/flocculation treatment, special attention was paidto the effect of pH, coagulant and flocculant doses. Then, effect of zero valent iron was also studied alone and in combination with coagulation/flocculation pretreatment. Our results indicate high removal efficiencies by coagulation/flocculation (46% COD and 63% turbidity) and Fenton process (48% COD and 76% turbidity). The combined application of coagulation/flocculation and Fenton revealed higher COD removal (62%) and turbidity reduction (90%). These results showed the applicability of this combined treatment method for the degradation of organic compounds and reduction of the treated leachate toxicity.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 139-153
Keywords: ochrona środowiska; inżynieria środowiska